Stress and Glucocorticoids Impair Memory Retrieval via β(2)-Adrenergic, G(i/o)-Coupled Suppression of cAMP Signaling - Schutsky, Keith (Society for Neuroscience, 2011)
Acute stress impairs the retrieval of hippocampus-dependent memory, and this effect is mimicked by exogenous administration of stress-responsive glucocorticoid hormones. It has been proposed that glucocorticoids affect memory by promoting the release and/or blocking the reuptake of norepinephrine (NE), a stress-responsive neurotransmitter. It has also been proposed that this enhanced NE signaling impairs memory retrieval by stimulating β(1)-adrenergic receptors and elevating levels of cAMP. In contrast, other evidence indicates that NE, β(1), and cAMP signaling is transiently required for the retrieval of hippocampus-dependent memory. To resolve this discrepancy, wild-type rats and mice with and without gene-targeted mutations were stressed or treated with glucocorticoids and/or adrenergic receptor drugs before testing memory for inhibitory avoidance or fear conditioning. Here we report that glucocorticoids do not require NE to impair retrieval. However, stress- and glucocorticoid-induced impairments of retrieval depend on the activation of β(2) (but not β(1))-adrenergic receptors. Offering an explanation for the opposing functions of these two receptors, the impairing effects of stress, glucocorticoids and β(2) agonists on retrieval are blocked by pertussis toxin, which inactivates signaling by G(i/o)-coupled receptors. In hippocampal slices, β(2) signaling decreases cAMP levels and greatly reduces the increase in cAMP mediated by β(1) signaling. Finally, augmenting cAMP signaling in the hippocampus prevents the impairment of retrieval by systemic β(2) agonists or glucocorticoids. These results demonstrate that the β(2) receptor can be a critical effector of acute stress, and that β(1) and β(2) receptors can have quite distinct roles in CNS signaling and cognition.